Hubungan Antar Sifat Jagung Manis yang Dibudidayakan Secara Organik - Lorenza, Eviya; Chozin, Mohammad; Setyowati, Nanik (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
Capability of growing well under organic conditions is prerequisite for a sweet corn variety to provide high yield under organic cropping management. Therefore, development of high yielding sweet corn varieties for organic cropping system would require sufficient information on the association among the growth traits to facilitate the determination of criteria in the selection program. Objective of this study was to estimate the degree of association among plant growth and developmental traits, in terms of phenotypic and genotypic correlations, in 64 genotypes generated from a complete diallel cross of 8 inbred lines under organic cropping system. Study was conducted from January-March 2016 on Ultisol of Medan Baru, Kandang Limun, sub-district of Muara Bangkahulu, City of Bengkulu at 10 m above sea level. A randomized complete block design with three replications to allocate the genotypes on double row plots with 4 length and 20 cm planting space. No agrochemical inputs was applied in cultural practices. Data were collected for plant height,stem diameter, leaf area, leaf number, tasseling date, and silking date. Analysis of variance was performed to determine the significant variation among the genotype. The degree of association among trait was estimated by both phenotypic and genotypic correlations analysis. Analysis of variance showed significant variation for all observed traits. High phenotypic and genotypic correlations were revealed between the growth traits (plant height, stem diameter, leaf area, and leaf number) and between the developmental traits (tasseling date, and silking date). However, the growth traits showed low correlation to the developmental traits.